Why Institutions Matter: Analysis of Their Significance in Shaping Economic, Environmental, And Policy Transformation - Botah, Kwadwo Yeboah (Pencerah, 2024)
The role of institutions in shaping societal systems and responding to complex global challenges has gained increased attention in recent decades. Institutions have functioned to shape the development and sustainability of society. Nevertheless, numerous institutionally-led challenges that restrict and alter sustainability and development across various aspects of society have also emerged. While institutional importance is widespread, their relationship with development is debated and contested. Through a systematic review approach, this paper explores the concept of institutions to understand whether they matter for development and examine their relevance within economic, policy, and environmental structures. The study indicates that indeed institutions play a significant role in accelerating economic, policy, and environmental growth across space and time. It demonstrates how it drives policy cycles, fosters economic progress, and shapes environmental transition. The study reveals that institutions create order, facilitate innovation, drive market transactions, and environmental security by mitigating conflicts, enforcing regulations, enhancing cooperation, ensuring the distribution of resources, and promoting sustainable ecological guidelines. However, complexities in their functions, structures, and adaptation exist, which can stimulate instabilities, stagnation, and decline in societal progression. Achieving enhanced institutional capacity toward societal development and progress thus requires unwavering political commitment, innovative actions, and coordinated decision-making.